2015
DOI: 10.1016/j.biomaterials.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific cardiovascular progenitor cells derived from integration-free induced pluripotent stem cells for vascular tissue regeneration

Abstract: Tissue-engineered blood vessels (TEBVs) are promising in regenerating a live vascular replacement. However, the vascular cell source is limited, and it is crucial to develop a scaffold that accommodates new type of vascular progenitor cells and facilitates in vivo lineage specification of the cells into functional vascular smooth muscle cells (VSMCs) to regenerate vascular tissue. In the present study, integration-free human induced pluripotent stem cells (hiPSCs) were established from patient peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…In this study, we adopted the in vitro monolayer VSMC differentiation system by differentiating human embryonic stem cells (hESCs) H1 cell line into VSMCs through cardiovascular progenitor cells (CVPCs) lineage . Since myocardin is the most potent driver for VSMC differentiation and YAP has been showed to abolish myocardin's function majorly by protein‐protein interaction , we hypothesized that YAP would inhibit the differentiation of CVPCs to VSMCs by inhibiting the function of myocardin.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we adopted the in vitro monolayer VSMC differentiation system by differentiating human embryonic stem cells (hESCs) H1 cell line into VSMCs through cardiovascular progenitor cells (CVPCs) lineage . Since myocardin is the most potent driver for VSMC differentiation and YAP has been showed to abolish myocardin's function majorly by protein‐protein interaction , we hypothesized that YAP would inhibit the differentiation of CVPCs to VSMCs by inhibiting the function of myocardin.…”
Section: Introductionmentioning
confidence: 99%
“…The TEVGs displayed a function in vivo when engrafted into severe combined immunodeficiency mice. Patient-specific integration-free hiPS cells have been developed using episomal vector nucleofection to specifically reprogram non-lymphoid cell subpopulation of peripheral blood mononuclear cells (Hu et al 2015). The iPS cells established by improved reprogramming efficiency were then differentiated into mesoderm-derived cardiovascular progenitor cells.…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%
“…80 One group used patient peripheral blood mononuclear cell-derived hiPSCs, for differentiation into cardiovascular progenitors via a mesodermal intermediate that were the seeded onto a porous nanofibrous scaffold for subcutaneous implantation into nude mice. 81 After 2 weeks, histological analysis revealed that >80% of fluorescence-labeled progenitor cells were positive for SM22α. In vitro studies showed that differentiation of these patient-specific, integration-free iPSCs with PDGF-BB and TGF-β supplementation resulted in a cell population capable of contracting in response to the muscarinic receptor agonist, carbachol, as seen with primary human aortic smooth muscle cells.…”
Section: Tissue-engineered Blood Vesselsmentioning
confidence: 99%
“…The authors of this study deliberately avoided using EB formation to derive VSMCs, to reduce the likelihood of generating a heterogeneous population of VSMCs from multiple germ layers, which would result in a VSMC population lacking the distinctive physiological properties of lineage-specific VSMCs. 50,81 Moreover, a nonviral method of reprogramming peripheral blood mononuclear cells for iPSC generation reduces the tumorigenesis risk associated with using lentivirus-based iPSCs for in vivo studies. 82,83 Alternative tissue-engineered vessel studies have included the use of bilayered collagen scaffolds for iPSC-VSMC seeding.…”
Section: Tissue-engineered Blood Vesselsmentioning
confidence: 99%